Problematika Profesi Debt Collector Menurut Pandangan Islam - Chindy Wulandari; Rozalinda (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
This research aims to explain the problems of the profession as a debt collector in society. This profession is often considered a negative profession. As well as the Islamic view of this profession. Consumer protection is a term used to describe the legal protection given to consumers in their efforts to meet their needs from things that are detrimental to consumers. This type of research is qualitative research with this research approach included in the type of library research. Data was obtained from secondary data taken from books and journals. The data analysis technique uses content analysis and data is collected from reading, examining the thoughts of experts in various literature related to the research focus. Legal violations committed by debt collectors due to arbitrary actions against consumers or customers occurred because several debt collectors violated the rules set in carrying out their duties. On the other hand, there is also a lack of public knowledge regarding the legal umbrella that covers them. Even in Islam, the profession of debt collector is not a haram or prohibited job in Islam. Because a debt collector is a wakalah or representative of the tasks that have been entrusted to them.